The Role of Granzyme B Activity and Concentration, and Serpin B9 Concentration with Hepatocellular Carcinoma in Patients with Chronic Hepatitis B Virus - Hussein S. Alshamary, Qasim S. Al-Mayah, Fadhil Abdulla Abdul-Ridha (Pakistan Journal of Medical & Health Sciences, 2022)
Backgrounds: Granzyme B (GzmB) is the main effective weapon of adaptive immune response that involved in killing of the infective as well as cancerous cells. Serum concentration and/or activity of GzmB may influence the course of chronic hepatitis B (CHB). Aims of the study: To investigate the role of serum level of GzmB and its activity as well as the effect of serpin B9 inhibitor on serum level of GzmB in patients with HCC. Patients and Methods: This is a cross-sectional study which included 85 patients with CHB. Those patients were divided into two groups: Group 1: includes 45 patients diagnosed with HCC, group 2: includes 40 Patients without HCC. Demographic data of the patients were collected from direct interview. Liver function test were measured spectrophotometrically. Granzyme B activity was estimated using spectrophotometry. Enzyme linked immunosorbent assay was used to measure Granzyme B concentration, serum level of and serpin B9. Results: Patients without HCC had significantly higher activity (median: 58 pmol, range: 34.0-130.0 pmol) and concentration (median; 31 pg/ml, range: 0.0-383.0 pg/ml) than those without HCC (median activity: 26, range: 7.0-63.0, median concentration: 18.7 pg/ml, range: 0.0-52.0 pg/ml) with highly significant differences. Conclusions: Granzyme B activity and concentration are significantly reduced in CHB patients with HCC compared with those without HCC. Thus, the reduction in GzmB activity cannot be attributed to increase Serpin B9, rather the GzmB polymorphism may be the main effector.